Aspirations, austerity and agency: adult women learners in the English FE sector and the capacity to aspire in an austerity context - Suart, Rebecca Mary (2021)
The Kennedy review (1997) prompted a dramatic rise in the number of adult women learners in Further Education (FE), which at its peak reached almost 3 million. However, a narrowing of policy goals and austerity cuts over the past fifteen years have seen this figure plummet by more than half. In the context of productivity and austerity, women learners who do not immediately progress into employment are deemed a poor return on investment. And yet, it is somewhat surprising that given the sharp cuts to the sector, as well as their gradual erasure from policy discourse and research, adult women continue to represent the majority of all learners in FE. Against this harsh backdrop, it is important to understand why women return to FE and VET and what they hope to gain from doing so. Located within a feminist inquiry, this longitudinal study aims to understand the aspirations of women learners, how they are shaped by past experiences and the ways that they navigate towards their goals. The in-depth narrative interviews with twenty- one women learners on a range of VET programmes, provides a rich understanding of the complex nature of aspirations and how these are shaped by their biographies. The complex and dynamic nature of women learners’ aspirations have been conceptualised using Arjun Appadurai’s ‘capacity to aspire’ (2004) and Debraj Ray’s ‘aspirations window’ (2006), along with feminist economics theories on the gendered constraints on choice and agency.